PENGARUH DIVIDEND PAYOUT, PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, KEPEMILIKAN MANAGERIAL, KEPEMILIKAN INSTITUSIONAL DAN ALIRAN KAS BEBAS TERHADAP KEBIJAKAN HUTANG - BENY BENY (Jurnal Bisnis dan Akuntansi, 2013)
The purpose of this research is to identify the influence of dividend payout, profitability, firm growth, managerial ownership, institutional ownership, and free cash flow on debt policy. Sample in this research is manufacturing company which are listed in Indonesian Stock Exchange between the years of 2006-2009. This reseacrh uses purposive sampling method, normality test, classic assumption, multiple regression, and simple regression method to see the contribution of each variable in influence debt policy. The result of this research showed that institutional ownership, profitability, and free cash flow have influence toward debt policy. Other independent variables they are managerial ownership, dividend payout, and firm growth do not have influence toward debt policy